Joint BAP NAPICU evidence-based consensus guidelines for the clinical management of acute disturbance: De-escalation and rapid tranquillisation. (June 2018) - Patel, Maxine X; Sethi, Faisil N; Barnes, Thomas RE; Dix, Roland; Dratcu, Luiz; Fox, Bernard; Garriga, Marina; Haste, Julie C; Kahl, Kai G; Lingford-Hughes, Anne; McAllister-Williams, Hamish; O'Brien, Aileen; et al.
The British Association for Psychopharmacology and the National Association of Psychiatric Intensive Care and Low Secure Units developed this joint evidence-based consensus guideline for the clinical management of acute disturbance. It includes recommendations for clinical practice and an algorithm to guide treatment by healthcare professionals with various options outlined according to their route of administration and category of evidence. Fundamental overarching principles are included and highlight the importance of treating the underlying disorder. There is a focus on three key interventions: de-escalation, pharmacological interventions pre-rapid tranquillisation and rapid tranquillisation (intramuscular and intravenous). Most of the evidence reviewed relates to emergency psychiatric care or acute psychiatric adult inpatient care, although we also sought evidence relevant to other common clinical settings including the general acute hospital and forensic psychiatry. We conclude that the variety of options available for the management of acute disturbance goes beyond the standard choices of lorazepam, haloperidol and promethazine and includes oral-inhaled loxapine, buccal midazolam, as well as a number of oral antipsychotics in addition to parenteral options of intramuscular aripiprazole, intramuscular droperidol and intramuscular olanzapine. Intravenous options, for settings where resuscitation equipment and trained staff are available to manage medical emergencies, are also included.